Design of an Electronic Assessment to Assess Students' Critical Thinking Abilities on Static Fluid Material - Amelia zelika Herawan; Fatni Mufit; Festiyed Festiyed; Selma Riyasni (Physics Learning and Education, 2025)
Assessment of students’ critical thinking abilities is a crucial component of 21st-century learning. This study aims to design an electronic assessment instrument to evaluate students’ critical thinking skills in the topic of static fluid using a summative assessment approach. The instrument consists of twenty multiple-choice questions developed based on Ennis’s critical thinking indicators. The research employed the Plomp model, which includes three stages: preliminary research, prototyping, and assessment development. Validation by three experts indicated a high level of validity (Aiken’s V = 0.83), while the practicality test showed positive responses from both students (83.9) and teachers (88.4). The reliability coefficient was 0.75 (high category), with items categorized as easy to moderate in difficulty and adequate in discrimination power (0.36). This study contributes by providing a digital-based assessment tool that supports the measurement of higher-order thinking in physics education. However, the study was limited by a small sample size and testing conducted only on static fluid material. Future research is recommended to expand the sample and apply the instrument across different physics topics to enhance its generalizability.